Iron metabolism in field hockey players during an annual training cycle - Podgorski, T.; Krysciak, J.; Konarski, J.; Domaszewska, K.; Durkalec-Michalski, K.; Strzelczyk, R.; Pawlak, M. (Journal of Human Kinetics, 2015)
Post-physical training changes in iron metabolism in the human body often occur. To fully describe these processes, fifteen male Polish National Team field hockey players (age 27.7 ± 5.2 years, body mass 72.8 ± 7.6 kg and body height 177.1 ± 5.7 cm) were examined in three phases of an annual training cycle: preparatory (T1), competitive (T2) and transition (T3). To assess aerobic fitness, maximal oxygen uptake (VO2max) was evaluated. Based on the iron concentration, the changes in total iron binding capacity (TIBC), unsaturated iron binding capacity (UIBC) and other selected haematological indicators (haemoglobin, erythrocytes, mean corpuscular haemoglobin - MCH) in iron metabolism were estimated. The average values of maximum oxygen uptake increased from 54.97 ± 3.62 ml·kg-1·min-1 in T1 to 59.93 ± 3.55 ml·kg-1·min-1 in T2 (p<0.05) and then decreased to 56.21 ± 4.56 ml·kg-1·min-1 in T3 (p<0.05). No statistically significant changes in the erythrocyte count were noted. The MCH and haemoglobin concentration decreased between T1 and T2. The maximal exercise test caused a significant (p<0.05) increase in the plasma iron concentration during the competition and transition phases. Progressive but non-significant increases in resting iron concentration, TIBC and UIBC in the analysed annual training cycle were noted. To show global changes in iron metabolism in the human body, it is necessary to determine additional variables, i.e. UIBC, TIBC, haemoglobin, MCH or the erythrocyte count. The direction of changes in iron metabolism depends on both the duration and intensity of the physical activity and the fitness level of the subjects. Dietary intake of iron increases the level of this trace element and prevents anaemia associated with training overloads.